2020
DOI: 10.1002/hbm.25313
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus transformation into motor action: Dynamic graph analysis reveals a posterior‐to‐anterior shift in brain network communication of older subjects

Abstract: Cognitive performance slows down with increasing age. This includes cognitive processes that are essential for the performance of a motor act, such as the slowing down in response to an external stimulus. The objective of this study was to identify aging‐associated functional changes in the brain networks that are involved in the transformation of external stimuli into motor action. To investigate this topic, we employed dynamic graphs based on phase‐locking of Electroencephalography signals recorded from heal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…However, the direct test for hemispheric asymmetry yielded no significant results ( Figure 5B ,b). Hemispheric asymmetry reduction in older adults has been reported during cognitive tasks across studies ( Hogan et al, 2012 ; Learmonth et al, 2017 ; Kenney et al, 2019 ; Rosjat et al, 2021 ). The here presented results do not show an apparent HAROLD effect.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…However, the direct test for hemispheric asymmetry yielded no significant results ( Figure 5B ,b). Hemispheric asymmetry reduction in older adults has been reported during cognitive tasks across studies ( Hogan et al, 2012 ; Learmonth et al, 2017 ; Kenney et al, 2019 ; Rosjat et al, 2021 ). The here presented results do not show an apparent HAROLD effect.…”
Section: Discussionmentioning
confidence: 93%
“…Due to the close link between reward processing and cognition, we propose the involvement of HAROLD, PASA, and FPCN compensatory mechanisms in preserved reward system function in healthy aging. These compensatory models have been tested successfully with EEG connectivity analyses elsewhere ( Rosjat et al, 2018 ; Rosjat et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These compensatory phenomena are found not only in cognitive tasks but also in motor tasks. For example, Rosjat et al ( 2021 ) showed increases in delta and theta synchrony (measured by PLV) in healthy elderly in association with sustained motor performance at the same level as in young people (see also Rosjat et al, 2018 ).…”
Section: Normal Agingmentioning
confidence: 99%